Dampak Kualitas dan Harga Rumah terhadap Minat dan Keputusan Pembelian Perumahan Berdasarkan Perspektif Masyarakat di Kelurahan Simalingkar B Medan Johor - Adrian Simatupang, Simeon; Ira Natalanta Lumban Gaol; Umamah, Nur; Dewi Lubis, Putri Kemala (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This article aims to examine the impact of house quality and price on interest in purchasing housing, with a focus on the consumer perspective in Simalingkar B Village There were 15 respondents interviewed . This research is qualitative research with data collection methods by conducting interviews and the method used in preparing this journal is the descriptive method through literature review or literature review. Journal preparation is carried out through literature review, namely by reviewing and analyzing books and scientific journals that have been published. The results of our interviews with people in Simalingkar B Village show that their decision to buy a house is strongly influenced by the price and quality of the house. Price is very important because it contributes to a buyer's decision to purchase a home. Improving the quality of houses must also be improved because the quality of houses greatly influences buyers' decisions to buy housing. People in Simalingkar B Subdistrict show that making the decision to buy a house is a decision that is carefully thought out and made after much consideration. Quality and price remain the main considerations. Apart from the Simalingkar B community's desire for high-quality houses, affordable prices commensurate with quality are the keys to attracting buyers.